Custom ocular prosthesis with modification in impression and iris button for rehabilitation of post-enucleation eye defect: a case report - Kriswandy Putra; Putri Welda Utami Ritonga; Haslinda Z. Tamin (Indonesia Prosthodontic Association, 2022)
Loss of eye have physiologic and social impact on patients, especially in pediatric patients. To overcome this problem ocular prosthesis can be made similar with the color, shape, size and movement of the patient’s eye, so the ocular prosthesis can look like natural eye. The various methods, techniques and concepts documented in this case re-port with modifications to the physiologic impression and making of iris buttons aim to get the better movement of the prosthesis and 3D profile of the iris. A 6-years-old female patient came to the USU Dental Hospital to fabricate a new eye prosthesis. The patient had a medical history of retinoblastoma at the age of 2 years and had enucleation surgery. The eye is rehabilitated with fabrication of a custom ocular prosthesis with modifications on physiologic im-pression and iris button making. Modifications to physiologic impression and modifications to the fabrication of iris buttons will provide movement, shape and 3D effects of iris that are better than stock eye prosthesis. It is concluded that custom ocular prosthesis with modification on physiologic impression provide a better and more natural move-ment. While modification on making iris button using customized iris button cuvette will facilitate the process of ma-king iris button.